Eurospeak and the Russian terminology of law: translation challenges - I. N. Fomina (Дискурс профессиональной коммуникации, 2019)
The paper focuses on translation challenges arising from a discrepancy between English and Russian terminological systems of law and politics and studies the possible solutions used by translators. Advantages and drawbacks of the generally accepted methods are considered, as well as the factors that usually influence the translator’s decision.The study also aims at analysing the consequences of the translators’ choices. While in the source language (SL) terms are largely coined by lawyers and scholars, in the target language (TL) translators are often the people who introduce and popularise them, which makes them particularly responsible for their work. The paper provides an overview of the interaction between individual decisions made by translators and the long-term influence they make on the system of the Russian EU-related terminology.The findings of the study can be used in training translators, interpreters and other professionals in the fields of law and politics whose responsibilities require good command of the terminology in question. Further research in this area can make a strong contribution to the efforts of terminology management.